Obesity and Cardiometabolic Risk Stratification in Schoolchildren from Santa Clara - Elizabeth Fernández Martínez; Clara Luz Rodríguez Cervera; Emilio González Rodríguez; Yosvani García Nóbrega; Alianny Rodríguez Urrutia; Merlin Gari Llanes (Revista Finlay, 2022)
Background: noncommunicable diseases have been among the leading causes of morbidity and mortality in the world and in Cuba for more than 20 years. These include: obesity, high blood pressure and diabetes mellitus. These pathologies appear from childhood and their prevention must begin from an early age. Objectives: to determine obesity, stratify cardiometabolic risk and promote healthy lifestyles in schoolchildren from Santa Clara. Methods: an epidemiological, descriptive investigation with a cross-sectional design was carried out on 959 schoolchildren between 8 and 12 years of age in Santa Clara and between 2012 and 2020. Computer programs were developed, which allowed studying obesity and calculating body mass indexes, waist -hip and waist-height. Variables were included such as: age, sex, skin color, weight, height, waist circumference, hip circumference, blood pressure, personal and family pathological history, clinical laboratory tests, electrocardiograms and echocardiograms. Double-entry contingency tables were used to record the frequency of appearance of the values of two variables simultaneously. Non-parametric tests were applied, such as Chi Square for factor independence and proportion difference hypothesis test for independent groups. Results: 17.94 % of schoolchildren were overweight and 15.95 % obese. 4.48 % were moderately obese and 9.18 % were severely obese. The means of cholesterol, triglycerides and uric acid increased with the degree of obesity. Cardiometabolic risk estimates were developed in Android and WEB formats. Conclusions: there are high percentages of obese and overweight. The waist-hip ratio was the best predictor of cardiometabolic risk in the study conducted in Santa Clara. Greater clinical and educational intervention is required, which guarantees the adoption of healthier lifestyles.